2017
DOI: 10.18697/ajfand.77.15815
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition knowledge and food consumption practices and barriers in rural Ghana: The case of foods for preventing vitamin A and iron deficiencies

Abstract: Food-based approaches such as dietary diversification, nutrient retention and biofortification combined with nutrition education can be effective in eliminating micronutrient deficiencies. The objective of this study was to assess the nutrition knowledge and consumption practices as well as barriers to consumption with specific focus on food-based approaches to vitamin A and iron deficiencies prevention and to identify individual, community and governmental level strategies that may facilitate the adoption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…This might suggest that most adolescents are not interested in reading food labels. A greater proportion of the participants indicated that cocoyam leaves (“ Kontomire ”) and turkey berries (“ Kwahu nsusua” ) were the main sources of iron as reported by Omari et al., (2017) findings in rural communities in Ghana. Perhaps, health educators and guardians might be promoting these foods as iron‐rich in most rural communities.…”
Section: Discussionmentioning
confidence: 65%
“…This might suggest that most adolescents are not interested in reading food labels. A greater proportion of the participants indicated that cocoyam leaves (“ Kontomire ”) and turkey berries (“ Kwahu nsusua” ) were the main sources of iron as reported by Omari et al., (2017) findings in rural communities in Ghana. Perhaps, health educators and guardians might be promoting these foods as iron‐rich in most rural communities.…”
Section: Discussionmentioning
confidence: 65%
“…Food groups such as eggs, pulses, nuts and seeds, dark green vegetables and other vitamin A-rich fruits and vegetables and other fruits were seldom consumed and from our studies, the diet of the majority is quite monotonous, energy-dense, and lack nutrients. Several studies have reported the over-dependence on cereal and root-based staples in Ghana [ 52 54 ]. Thus, their dietary patterns predicted an insufficient intake of micronutrients as well as fiber which explains the high rate of inadequate dietary diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Some foods are sometimes tagged as poor people’s foods [23], and thus are deliberately ignored. Lack of knowledge of the nutritional and health benefits of certain foods makes some people, the educated and uneducated alike, disregard these foods [24,25]. This may not be different in the case of Ghana following statistical evidence of nutrient deficiencies, despite the availability of both domesticated and wild fruits in the various parts of the country.…”
Section: Introductionmentioning
confidence: 99%